2020
DOI: 10.1002/wps.20755
|View full text |Cite
|
Sign up to set email alerts
|

Association of preceding psychosis risk states and non‐psychotic mental disorders with incidence of clinical psychosis in the general population: a prospective study in the NEMESIS‐2 cohort

Abstract: The validity and clinical utility of the concept of “clinical high risk” (CHR) for psychosis have so far been investigated only in risk‐enriched samples in clinical settings. In this population‐based prospective study, we aimed – for the first time – to assess the incidence rate of clinical psychosis and es­timate the population attributable fraction (PAF) of that incidence for preceding psychosis risk states and DSM‐IV diagnoses of non‐psychotic mental disorders (mood disorders, anxiety disorders, alcohol use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 57 publications
3
60
0
Order By: Relevance
“…For the case-control analyses, as utilised in previous studies (Guloksuz et al ., 2019; Guloksuz et al ., 2020), ES-SCZ and PRS-SCZ were dichotomised at the quartile cut-off points based on the control distribution within each country (to account for differences between countries that may arise due to ethnic and geographical variation). The highest quartile was considered the binary risk state for schizophrenia (hereafter PRS-SCZ 75 and ES-SCZ 75 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case-control analyses, as utilised in previous studies (Guloksuz et al ., 2019; Guloksuz et al ., 2020), ES-SCZ and PRS-SCZ were dichotomised at the quartile cut-off points based on the control distribution within each country (to account for differences between countries that may arise due to ethnic and geographical variation). The highest quartile was considered the binary risk state for schizophrenia (hereafter PRS-SCZ 75 and ES-SCZ 75 ).…”
Section: Methodsmentioning
confidence: 99%
“…weighted estimates of individual exposures from meta-analyses or simple summation of exposures. Recent studies indicate that the ES-SCZ is associated with psychosis risk states (Guloksuz et al ., 2020) as well as mental and physical health (Pries et al ., 2020b) in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the schizophrenia PRS identified and discriminated healthy individuals from individuals with first episode psychosis, schizophrenia and other psychoses [46][47][48][49][50]. More recently, Perkins et al (2020) [51] reported that the schizophrenia PRS discriminated psychosis converters from non-converters in an at-risk sample of European ancestry, while He et al (2019) [52] found no association between schizophrenia PRS and conversion to psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Early psychopathology consists of a pluripotent mixed bag of phenotypic expressions that follow diverse trajectories defying traditional diagnoses. However, psychiatry has constructed balkanized frameworks modeled after traditional diagnostic silos, such as the clinical high-risk concept 4,5 . More recently, the transdiagnostic clinical staging model has been introduced to capture heterogeneity in clinical and functional outcomes, in order to improve prediction and prevention of illness progression 6 .…”
mentioning
confidence: 99%
“…This situation is further exacerbated by the frequent co-occurrence of drug use disorders with other mental health conditions (dual disorders) 2 , a phenomenon associated with increases in emergency department admissions 3 and psychiatric hospitalizations 4 , higher risk of relapse to drug use 5 , and increased likelihood of premature deaths 6 , including those resulting from suicide 7 . The individual, social and public health impact of dual disorders is very high, and a multidisciplinary and comprehensive response to the needs of persons with these disorders is required.…”
mentioning
confidence: 99%